2020
DOI: 10.3126/janr.v3i1.27153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of open pollinated and hybrid maize varieties in Dhading district of Nepal

Abstract: Five maize varieties namely Rampur composite, Arun-2, Manakamana-3, Rampur Hybrid-4 and Rajkumar were evaluated in randomized complete block design with four replications at farmers field at Nilkantha Municipality-09, Aashikhola, Dhading from February 2018 to June 2018 to identify high yielding maze  varieties. Significant variation  was observed for grain yield, silking and tasseling, number of kernels per cob and cob length.The largest cob length was found in Rampur composite (19.550 cm) and highest number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
4
2
0
Order By: Relevance
“…The mean data of research finding indicated that significantly (p<0.001) highest grain yield (5.32 t ha -1 ) obtained in Rajkumar which was at equivalence with Rampur Hybrid-10 (4.75 Mt ha -1 ) and Rampur composite (4.58 t ha -1 ). The result is in agreement with (Devkota et al, 2020) and lowest grain yield (2.33t ha -1 ) obtained in Arun-4. Grain and biological yield were lower in Arun-4 variety.…”
Section: Grain Yieldsupporting
confidence: 90%
“…The mean data of research finding indicated that significantly (p<0.001) highest grain yield (5.32 t ha -1 ) obtained in Rajkumar which was at equivalence with Rampur Hybrid-10 (4.75 Mt ha -1 ) and Rampur composite (4.58 t ha -1 ). The result is in agreement with (Devkota et al, 2020) and lowest grain yield (2.33t ha -1 ) obtained in Arun-4. Grain and biological yield were lower in Arun-4 variety.…”
Section: Grain Yieldsupporting
confidence: 90%
“…Highly significant differences in the ear length for genotypes were seen (Table 2) . References [ [33] , [34] , [35] ] also reported similar results. Bioseed 9220 was longer than all the genotypes in ear length while Khumal Hybrid 2 and Rajkumar were found statistically at par.…”
Section: Resultssupporting
confidence: 63%
“…The highest number of kernels row −1 was recorded for Bioseed 9784, Star 9 and Godavari whereas the lowest for TX 369. References [ 35 , 37 ] reported similar results for number of kernel rows cob −1 and kernels row −1 .…”
Section: Resultssupporting
confidence: 54%
“…Comparably, the highest plant height and ear height of 307.2 cm and 184 cm was reported in ZH191065 and the lowest plant height and ear height of 227.6 cm and 99.2 cm were reported in ZH 191158, respectively. Tis stipulates that the genotypes were varied from parent lines, and usage of commercial and local checks [9] which are also from varied parental lines may have contributed to the variation in the plant height and ear height while statistically being at par. A higher ear aspect was found in ZH191037 and ZH 192050 (2.6) and the lowest was found in ZH191065 (1.5) and shows variability among genotypes.…”
Section: Agromorphometric Characteristics Of Genotypesmentioning
confidence: 99%
“…Te yield potential of OP cultivars was much higher than the national average yields in the previous year, but hybrid cultivars today often out-yield OP cultivars by more than half to double or more [7], having high yields of at least 15% above that of common OP cultivars and up to 90% of hybrid yields [7,8]. According to the study report of [9], open-pollinated and hybrid maize varieties in Dhading district found maize genotype Rampur hybrid-4 was high yielding and most benefcial as compared to others. Apart from this, there is no guarantee of getting a hybrid seed of adopted hybrid in the region because seed suppliers keep on changing such hybrids based on their availability from suppliers.…”
Section: Introductionmentioning
confidence: 99%